Alcohol Use and Sexual Risk Behaviors Among Adolescents With Psychiatric Disorders: A Systematic Review and Meta-Analysis. Issue 5 (3rd September 2017) - Cunningham, Karlene; Martinez, David A.; Scott-Sheldon, Lori A. J.; Carey, Kate B.; Carey, Michael P.
ABSTRACT: Adolescents with psychiatric disorders appear to be at increased risk for acquiring HIV and other sexually transmitted infections; however, little is known about the prevalence of behavioral risk factors in this population. This meta-analysis aimed to assess the prevalence of alcohol use and sexual risk behaviors among adolescents with psychiatric disorders. Electronic database searches identified studies sampling adolescents diagnosed with psychiatric disorders and assessing both alcohol and sexual risk behaviors. Fourteen studies sampling 3, 029 adolescents with psychiatric disorders were included. The majority of adolescents with psychiatric disorders report alcohol use and sexual risk behaviors. Risk reduction interventions targeting these two behaviors are needed.